Self-concepts of first year "high" and "low" achievers at the Boys' and Girls' High School Departments of the Far Eastern University in relation to their academic achievement - Reventar, Nieves Potenciano 1926 (s.n.], 1966)
This is an analysis of the self-concepts of first year "high" and "low" achievers and the relationship between these self-concepts and their academic achievement. The author found that the self-concept scores of the "high" achievers are significantly higher than those of the "low" achievers.